Fed-Batch Operation for the Synthesis of Lactulose with ?-Galactosidase of Aspergillus Oryzae - Vera-Vera, C (Elsevier Ltd, 2017)
Fed-batch synthesis of lactulose from lactose and fructose with Aspergillus oryzae β-galactosidase was evaluated, obtaining a concentration of 40.4 g·L−1, which is 20% higher than obtained in batch, while the concentration of transgalactosylated oligosaccharides (TOS) was reduced by 98%. Therefore, selectivity of lactulose synthesis can be significantly higher by operating in fed-batch mode. The enzyme-limiting substrate mass ratio (E/S) is a critical variable in fed-batch operation. Higher values favor lactose hydrolysis over transgalactosylation, being 400 IU/g the limit for proper lactulose synthesis in fed-batch operation. Selectivity of lactulose synthesis increased with E/S being quite high at 800 IUH·g−1 or higher. However, this increase was obtained at the expense of lactulose yield. Lactulose synthesis in fed-batch operation was a better option than conventional batch synthesis, since higher product concentration and selectivity of lactulose over TOS synthesis were obtained. © 2017 Elsevier Ltd